ANALISIS HIGIENE DAN SANITASI LINGKUNGAN KERJA PADA PEKERJA RUMAHAN INDUSTRI SEPATU DI KABUPATEN SEMARANG - Qoni Mulia Sagita; Sulistyani Sulistyani; Yuliani Setyaningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Work environment is one of the important factors for workers to improve their productivity. Inadequate working environment can cause health problems. One of these can lead to work-related complaints. The aims of this study to determine the relationship of hygiene and sanitation working environment factors with work-related complaints on home workers in Semarang regency. This was an observational analytic study using cross sectional approach. Population in this study were all home worker in leather shoes industry in Semarang regency. The samples of 66 home workers were taken using stratified random sampling method. Data were analyzed using frequency distribution and Chi-Square test. The results of this study showed that there are some variables that have significant association with work-related complaints with p-value ≤ 0,05 including, length of work, duration of work, personal protective equipment (PPE) usage, light intensity, ventilation, and temperature. While the variables of age, body mass index (BMI), medical history, house wall, house floor, and occupancy density did not show significant association with work-related complaints with the p-value > 0,05. The Conclusions of this study were important to maintain hygiene and sanitation factors of the work environment because it can affect work-related complaints that may interfere the health of home workers. Homeworkers should increase the use of PPE, maintain their health condition by doing exercise and pay attention to the working environment conditions.